2002
DOI: 10.1128/iai.70.4.2151-2158.2002
|View full text |Cite
|
Sign up to set email alerts
|

Early Enhanced Th1 Response afterLeishmania amazonensisInfection of C57BL/6 Interleukin-10-Deficient Mice Does Not Lead to Resolution of Infection

Abstract: C3H and C57BL/6 mice are resistant to Leishmania major but develop chronic lesions with persistent parasite loads when they are infected with Leishmania amazonensis. These lesions develop in the absence of interleukin-4 (IL-4), indicating that susceptibility to this parasite is not a result of development of a Th2 response. Expression of the cytokine IL-10 during infection could account for the lack of IL-12 expression and poor cell-mediated immunity towards the parasite. Therefore, we tested the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
100
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 51 publications
(31 reference statements)
6
100
2
Order By: Relevance
“…Second, the use of an ERK inhibitor and anti-IL-10 neutralizing Ab failed to reverse the suppression of IL-12 production in infected DCs, despite their effectiveness in blocking IL-10 production, which suggested that IL-12 suppression by La parasites was IL-10-independent. Although IL-10-deficient mice were more resistant to L. major (Brooks et al, 2006;Kane and Mosser, 2001), deletion of the IL-10 gene did not change the susceptibility of mice to La parasites (Jones et al, 2002), suggesting to us that an IL-10-independent mechanism in persistent infection is caused by La infection. Accordingly, this study supports the view that amastigotes in the L. mexicana complex (La, L. mexicana, and L. pifanoi) can directly suppress the activation and/or accelerate the degradation of signaling pathways via their peptidases/ proteinases (Cameron et al, 2004), and that this delayed and suppressed DC activation is responsible for impaired innate and acquired immunity to parasite infection (Ji et al, 2003;Xin et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
“…Second, the use of an ERK inhibitor and anti-IL-10 neutralizing Ab failed to reverse the suppression of IL-12 production in infected DCs, despite their effectiveness in blocking IL-10 production, which suggested that IL-12 suppression by La parasites was IL-10-independent. Although IL-10-deficient mice were more resistant to L. major (Brooks et al, 2006;Kane and Mosser, 2001), deletion of the IL-10 gene did not change the susceptibility of mice to La parasites (Jones et al, 2002), suggesting to us that an IL-10-independent mechanism in persistent infection is caused by La infection. Accordingly, this study supports the view that amastigotes in the L. mexicana complex (La, L. mexicana, and L. pifanoi) can directly suppress the activation and/or accelerate the degradation of signaling pathways via their peptidases/ proteinases (Cameron et al, 2004), and that this delayed and suppressed DC activation is responsible for impaired innate and acquired immunity to parasite infection (Ji et al, 2003;Xin et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
“…IL-10 is not responsible for the lack of parasitism control or resolution of lesions, since there is no significant upregulation of this cytokine when lesions from L. amazonensis and L. major-infected mice start to differ. Moreover, no significant differences in the course of infection with L. amazonensis were found between wild-type and IL-10 knockout mice (Jones et al 2002, González-Lombana et al 2008. Accordingly, no increased expression of arginase was found when footpad lesions from mice infected with L. amazonensis or L. major was compared.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, when IFN-γ production is elevated by vaccination, a small but significant decrease in parasite levels is seen (Vanloubbeeck & Jones 2004, Hernández et al 2006, Hernández Sanabria et al 2007, González-Lombana et al 2008. It is interesting to notice that L. amazonensis fails to trigger a Th2 response in C57BL mice (Afonso & Scott 1993, Jones et al 2002, Ji et al 2003, Hernández et al 2006, even though lesions are quite severe and lead to necrosis and a loss of tissue. IL-10 is not responsible for the lack of parasitism control or resolution of lesions, since there is no significant upregulation of this cytokine when lesions from L. amazonensis and L. major-infected mice start to differ.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent study has shown that IL-10-deficient BALB/c mice can control infection with L. major, suggesting that IL-10 plays a critical role in mediating the susceptibility and pathogenesis of cutaneous leishmaniasis (16). However, C57BL/6 IL-10-deficient mice fail to exhibit increased resistance to L. amazonensis, despite the fact that they developed an enhanced Th1-type response (17). Given the differences in patterns of disease in inbred strains of mice infected with the Old World parasite, L. major, and the New World Leishmania species and given the relative importance of different cytokines in resistance or susceptibility to different Leishmania species, we have explored how a deficiency in IL-10 influences infection with L. mexicana and L. amazonensis in susceptible BALB/c mice.…”
mentioning
confidence: 99%